PENENTUAN EFISIENSI INHIBISI KOROSI BAJA MENGGUNAKAN EKSTRAK KULIT BUAH KAKAO (Theobroma cacao) - Sri Hermawan; Yuli Rizky Ananda Nasution; Rosdanelli Hasibuan (Talenta Publisher (Universitas Sumatera Utara), 2012)
Cocoa peel extract is a natural inhibitor that can be used to inhibit the corrosion reaction rate. This research begins by extracting cocoa pods by maceration followed by evaporation on rotary vacuum evaporator and extracts used as the inhibitor with concentration 600, 800 and 1000 ppm, using steel 1 × 2 cm and the thickness is 0,1 cm to determine the corrosion rate and corrosive medias are sea water, rainwater and sulfuric acid 1 M . The highest inhibition efficiency generated is 93,06% with concentration of 600 ppm inhibitor in rainwater corrosive media; which means that cocoa peel extract more efficiently used in rainwater corrosive media.